Archival Materials as a Source for Studying Detention Conditions and Child Mortality in the Kazakhstani Gulag Camps: A Case Study of Karlag - Saktaganova, Zauresh; Abdrakhmanova, Kymbat; Mazhitova, Zhanna; Khassenova, Zhazira; Kasenov, Yelaman; Serdkhan, Amanbek (Journal of Ecohumanism, 2024)
This article examines key aspects of the history of children in the Gulag. It provides insights into the archival funds and documents used for this study and offer a brief historiographical overview of the topic. Six categories of children who were in forced labour camps are identified, focusing on those who entered the camps in infancy alongside mothers convicted under “political” articles (including as members of the families of traitors to the motherland) or born to prisoner mothers. Drawing from documentary materials from the State Archives of the Russian Federation and the archives of the Karaganda corrective labour camps, the study clarifies the timeline, population, and conditions of children in Karlag. It outlines the reasons for the increase in the child population within Gulag camps, leading to the establishment of specialized infrastructure for children of imprisoned mothers in the early 1940s. The authors compared the conditions of detention for children of imprisoned mothers in infant homes and children of civilian workers in children’s homes. Extremely difficult conditions of detention for children of imprisoned mothers, extremely low levels of food and clothing allowances, and unsatisfactory arrangements for the baby’s home were noted. The study tracks the dynamics of infant homes, their resources, and healthcare levels in Karlag during the 1940s–1950s. Child mortality rates are analyzed by year, identifying causes, peak years, and conducting a comparative analysis of child mortality rates within the Gulag and Karlag. In conclusion, the study draws correlations between the dynamics of imprisoned children and the overall camp population.